Endoscopic Transnasal Trans-Sphenoidal Approach for Pituitary Adenomas: A Comparison to the Microscopic Approach Cohort by Propensity Score Analysis. Issue 3 (7th June 2019) - Castaño-Leon, Ana M; Paredes, Igor; Munarriz, Pablo M; Jiménez-Roldán, Luis; Hilario, Amaya; Calatayud, Maria; Hernandez-Lain, Aurelio; Garcia, Ester; Garcia, Alfredo; Lagares, Alfonso; Alén, Jose F
Abstract: BACKGROUND: Despite some evidence for the adoption of endoscopic transnasal trans-sphenoidal surgery (ETSS) for pituitary adenomas, the advantages of this technique over the traditional approach have not been robustly confirmed. OBJECTIVE: To compare ETSS with the microscopic sublabial trans-septal trans-sphenoidal surgery (MTSS) for pituitary adenomas. METHODS: We retrospectively reviewed 2 cohorts of ETSS and MTSS performed at our institution from 1995 to 2017. Patient characteristics, surgical data, and outcomes were recorded prospectively. We performed a univariate and multivariable analysis to determine the best surgical approach. To improve the quality of the results, we matched the distribution of patient characteristics between groups by propensity score (PS) method. RESULTS: A total of 187 procedures (90 MTSS, 97 ETSS) were reviewed. We found better results in the ETSS group in terms of gross total resection ( P  = .002) and hormone-excess secretion control ( P  = .014). There was also a lower incidence of cerebrospinal fluid leakage ( P  = .039), transitory diabetes insipidus ( P  = .028), and postoperative hypopituitarism ( P  = .045), as well as a shorter hospital length of stay ( P  < .001). After PS matching, we confirmed by multivariable logistic regression analysis an increased odds ratio of gross total resection for the ETSS (3.910; 95% CI 1.720-8.889; P  = .001). CONCLUSION: By PS method, our results suggest that the ETSS provides advantages over the traditional MTSS approach for tumor resection. Better control of secreting tumors and a lower rate of most complications also support the selection of the ETSS approach for the treatment of pituitary adenomas. Graphical Abstract: